Utilization of Strategic Instructional Module to Facilitate Comprehension in Organic Chemistry: An Experiment - Alice T Rivera (ASEAN Multidisciplinary Research Journal, 2020)
This study aimed to test the efficiency of developed and evaluated module in facilitating learning in organic Chemistry. Using experimental method of research, 33 males and 27 females from Grade 9 students were grouped into control and experimental group. Both groups were pre-tested. The control group was subjected to usual lecture discussion while the experimental group used the Strategic Instructional Module. The results of the pre-test showed that there was no significance difference in the performance of both groups. All the respondents of both groups had low academic performance on the topic Organic Chemistry. Post-test revealed that both groups improved their scores, however, there was a significant difference in the scores of the control and experimental group that use module approach. Experimental group obtained higher scores than   control group. This indicates that the utilization of the Strategic Instructional Module can help to facilitate learning and comprehension in Organic Chemistry. Across the gender, the study found out that male students have higher score than female. Based on the results of the study, the researcher recommends the necessity to use more modern means to teach students the "Science" domain such as module strategy.